PVC composite material, preparation method thereof and light strip

By adding nano-grade pottery, nano-active calcium carbonate, oxide and glass fiber to the PVC materials, combine with silicone materials and plasticizers, a soft lamp belt that does not harden at -40 ° C low temperatures at low temperatures at -40 ° C PVC composite materials solve the problem of hardening at low temperatures, and realize good softness and cold resistance.

CN118085469BActive Publication Date: 2025-01-28GUANGDONG QILONG TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311527028.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-16
Publication Date
2025-01-28
Estimated Expiration
2043-11-16

AI Technical Summary

Technical Problem

The existing soft light strip material cannot maintain its original softness at low temperatures of -40℃ and is prone to hardening.

Method used

A PVC composite material, which includes nano -grade pottery, nano -active calcium carbonate, oxide and glass fiber as a composite filler, combined with silicone materials, modifiers and plasticizers, and preparation through specific mixing and extruded processing process. Essence

Benefits of technology

At the low temperature of -40 ° C, the hardness of the PVC composite material remains unchanged, maintaining good softness and stretching strength, comfortable feel, and extending the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application provides a PVC composite material, a preparation method thereof and a light strip, the PVC composite material comprising the following components in parts by weight: 90‑120 parts of PVC powder; 8‑12 parts of composite filler; 60‑80 parts of plasticizer; 8‑12 parts of cold-resistant agent; 20‑30 parts of liquid rubber; 4‑8 parts of modifier; 0.5‑1.0 parts of silicone material; 0.1‑15 parts of other additives; the composite filler comprises nano-grade clay, nano-activated calcium carbonate, zirconium oxide and glass fiber. Adding composite fillers, silicone materials, modifiers and plasticizers to PVC powder improves the cold resistance and flexibility of the composite material, so that the hardness of the material remains unchanged in a low temperature environment, can be used normally at ‑40°C, and has good softness and silicone feel, and is comfortable to use; nano-grade clay, zirconium oxide and glass fiber can reduce thermal deformation of the material, so that the products of the PVC composite material can maintain the original design structure, increase practicality and service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of PVC materials, and more specifically, to PVC composite materials and preparation methods and applications thereof. Background Art

[0002] PVC, or polyvinyl chloride, is one of the world's largest plastic products. It is cheap and widely used. Polyvinyl chloride resin is a white or light yellow powder. Generally, it is not used alone and must be modified. PVC is an amorphous white powder with a small degree of branching and poor stability to light and heat. Different additives are added according to different uses, and polyvinyl chloride plastics can present different physical and mechanical properties.

[0003] PVC material can be used to make soft light strips. However, the soft light strip materials currently on the market cannot maintain their original softness at a low temperature of -40°C without hardening. In view of this, it is urgent to develop a new type of silicone-like soft light strip PVC material. Summary of the invention

[0004] Based on this, the purpose of this application is to provide a PVC composite material and its preparation method and application, so as to solve the technical problem in the prior art that the soft light strip material currently on the market cannot maintain its original softness without hardening at a low temperature of -40°C.

[0005] In order to achieve the above-mentioned invention object, the technical solution of this application is as follows:

[0006] In a first aspect, a PVC composite material is provided, comprising the following components in parts by weight:

[0007]

[0008]

[0009] The composite filler includes nano-grade clay, nano-active calcium carbonate, zirconium oxide and glass fiber.

[0010] Optionally, the mass ratio of nano-scale clay, nano-active calcium carbonate, zirconium oxide and glass fiber in the composite filler is (5-10):(8-15):(0.01-0.2):(0.01-0.1).

[0011] Optionally, the mass ratio of nano-scale clay, nano-active calcium carbonate, zirconium oxide and glass fiber in the composite filler is (6-8): (10-12): (0.05-0.1): (0.01-0.05).

[0012] Optionally, the PVC comprises Formosa Plastics S-70; and / or,

[0013] The plasticizer includes at least one of trioctyl trimellitate, trioctyl trimellitate, trihexyl trimellitate, and tetramethyl pyromellitate; and / or,

[0014] The cold-resistant agent includes cold-resistant agent 797S and / or epoxy 1,4-cyclohexanedimethanol dioleate.

[0015] Optionally, the modifier is a modifier TPR; and / or,

[0016] The silicone material is powdered vulcanized silicone.

[0017] Optionally, other additives include at least one of a stabilizer, a lubricant, a flame retardant, and an anti-UV agent.

[0018] Optionally, other additives include the following components in parts by weight: 2-4 parts of stabilizer, 0.1-0.5 parts of lubricant, 6-10 parts of flame retardant, and 0.4-0.8 parts of anti-UV agent.

[0019] Optionally, the stabilizer comprises stabilizer A-200P; and / or,

[0020] The lubricant is lubricant 316A; and / or,

[0021] The flame retardant is flame retardant DR-65; and / or,

[0022] The anti-UV agent includes at least one of UV-326, UV-531, and BASF C81.

[0023] In a second aspect, a method for preparing the above-mentioned PVC composite material is provided, comprising the following steps:

[0024] Mix PVC powder, composite filler, cold-resistant agent, liquid rubber, silicone material and other additives, gradually add modifier at 95°C-110°C, mix to obtain premix;

[0025] The premix is ​​mixed with the plasticizer at 75° C.-85° C., and then extruded through a single-screw extruder to obtain a PVC composite material.

[0026] In a third aspect, a light strip is provided, which is made of the above-mentioned PVC composite material.

[0027] The beneficial effects of this application are:

[0028] The PVC composite material provided by the present application adds composite fillers, silicone materials, modifiers and plasticizers to PVC powder to improve the cold resistance and flexibility of the composite material. Among them, the nano-active calcium carbonate in the composite filler is beneficial to improving the tensile strength and elongation at break performance of the PVC composite material, and at the same time, it synergizes with the silicone material and the plasticizer to improve the flexibility and bending strength of the material, so that the hardness of the material remains unchanged in a low temperature environment, and can be used normally at -40°C, and has good softness and silicone feel, and is comfortable to use; nano-grade clay, zirconium oxide and glass fiber can reduce thermal deformation of the material, so that the products of the PVC composite material can maintain the original design structure, increase practicality and service life;

[0029] The preparation method of the PVC composite material provided in the present application is formulated in accordance with the properties of the material and the reaction characteristics of each component, and is simple to operate and has high working efficiency;

[0030] The light strip provided in the present application is made of the PVC composite material of the present application, has good cold resistance, does not harden at a low temperature of -40°C, maintains good softness, as well as tensile strength and elongation at break performance, and feels comfortable. DETAILED DESCRIPTION

[0031] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0032] The present application provides a PVC composite material, comprising the following components in parts by weight:

[0033]

[0034]

[0035] The composite filler includes nano-grade clay, nano-active calcium carbonate, zirconium oxide and glass fiber.

[0036] The PVC composite material provided in the embodiment of the present application adds a composite filler, a silicone material, a modifier and a plasticizer to PVC powder to improve the cold resistance and flexibility of the composite material. Among them, the nano-active calcium carbonate in the composite filler is beneficial to improving the tensile strength and elongation at break performance of the PVC composite material, and at the same time, it synergizes with the silicone material and the plasticizer to improve the flexibility and bending strength of the material, so that the hardness of the material remains unchanged in a low temperature environment, and can be used normally at -40°C, and has good softness and silicone feel, and is comfortable to use; nano-grade clay, zirconium oxide and glass fiber can reduce thermal deformation of the material, so that the products of the PVC composite material can maintain the original design structure, increase practicality and service life.

[0037] In some embodiments, the mass ratio of nano-clay, nano-active calcium carbonate, zirconium oxide and glass fiber in the composite filler is (5-10): (8-15): (0.01-0.2): (0.01-0.1). By controlling the addition amount of nano-clay, nano-active calcium carbonate, zirconium oxide and glass fiber, the synergistic effect of nano-clay, nano-active calcium carbonate, zirconium oxide and glass fiber with silica gel material, modifier and plasticizer is adjusted to make the PVC composite material reach a good balance point of cold resistance, flexibility and thermal deformation. If the content of nano-clay, nano-active calcium carbonate, zirconium oxide and glass fiber is too high, the hardness of the PVC composite material may be too high, which affects the softness of the material; if the content of nano-clay, nano-active calcium carbonate, zirconium oxide and glass fiber is too low, the thermal deformation performance of the PVC composite material will be reduced. After experiments, it was found that when the mass ratio of nano-clay, nano-activated calcium carbonate, zirconium oxide and glass fiber was (5-10):(8-15):(0.01-0.2):(0.01-0.1), the cold resistance, flexibility, softness and thermal deformation of the PVC composite material achieved a good balance.

[0038] In some preferred embodiments, when the mass ratio of nano-scale clay, nano-activated calcium carbonate, zirconium oxide and glass fiber in the composite filler is (6-8):(10-12):(0.05-0.1):(0.01-0.05), the cold resistance, flexibility, softness and thermal deformation of the PVC composite material are better.

[0039] In some preferred embodiments, the PVC composite material is composed of the following components in parts by weight:

[0040]

[0041] The composite filler comprises nano-grade clay, nano-active calcium carbonate, zirconium oxide and glass fiber in a mass ratio of (6-8): (10-12): (0.05-0.1): (0.01-0.05).

[0042] In some embodiments, the PVC includes Formosa Plastics S-70.

[0043] In some embodiments, the plasticizer includes at least one of trioctyl trimellitate, trioctyl trimellitate, trihexyl trimellitate, and tetramethyl pyromellitate.

[0044] In some embodiments, the cold resistant agent includes cold resistant agent 797S and / or epoxy 1,4-cyclohexanedimethanol dioleate.

[0045] In some embodiments, the modifier is modifier TPR.

[0046] In some embodiments, the silicone material is powdered vulcanized silicone.

[0047] In some embodiments, other additives include at least one of a stabilizer, a lubricant, a flame retardant, and an anti-UV agent.

[0048] In some embodiments, other additives include the following components in parts by weight: 2-4 parts of stabilizer, 0.1-0.5 parts of lubricant, 6-10 parts of flame retardant, and 0.4-0.8 parts of anti-UV agent.

[0049] In some embodiments, the stabilizer includes Stabilizer A-200P.

[0050] In some embodiments, the lubricant is lubricant 316A.

[0051] In some embodiments, the flame retardant is flame retardant DR-65.

[0052] In some embodiments, the anti-UV agent includes at least one of UV-326, UV-531, and BASF C81.

[0053] The present application also provides a method for preparing the above-mentioned PVC composite material, comprising the following steps:

[0054] S1: PVC powder, composite filler, cold-resistant agent, liquid rubber, silicone material and other additives are mixed, and modifiers are gradually added at 95°C-110°C to obtain a premix.

[0055] Firstly, PVC powder, composite filler, cold-resistant agent, liquid rubber, silicone material and other additives are mixed to obtain a mixture, and then a modifier is added to obtain a modified premix.

[0056] In some embodiments, the mixing method of the components can be carried out in a high-speed mixer, wherein, during the process of gradually adding the modifier, the stirring speed of the high-speed mixer can be selected to be 200r / min-400r / min, and the stirring time can be 8-12min. The appropriate stirring time is selected according to the actual situation to ensure that the components are fully mixed.

[0057] S2: The premix and the plasticizer are mixed at 75° C.-85° C., and then extruded through a single screw extruder to obtain a PVC composite material.

[0058] In some embodiments, the premix and the plasticizer are mixed in a mixer, the stirring speed can be selected to be 20-40 r / min, and the stirring time is 8-12 min. The appropriate stirring time is selected according to the actual situation to fully mix the premix and the plasticizer.

[0059] The preparation method of the PVC composite material provided in the embodiment of the present application is formulated in accordance with the properties of the material and the reaction characteristics of each component, and has simple operation and high working efficiency.

[0060] The embodiment of the present application also provides a light strip, which is made of the above-mentioned PVC composite material.

[0061] The light strip provided in the embodiment of the present application is made of the PVC composite material of the embodiment of the present application, has good cold resistance, does not harden at a low temperature of -40°C, maintains good softness, as well as tensile strength and elongation at break performance, and feels comfortable.

[0062] The following examples are used to illustrate.

[0063] Example 1

[0064] The PVC composite material of this embodiment includes the following components in parts by weight:

[0065]

[0066]

[0067] The composite filler comprises nano-grade clay, nano-active calcium carbonate, zirconium oxide and glass fiber in a mass ratio of 6:10:0.01:0.02.

[0068] The preparation method of the above PVC composite material comprises the following steps:

[0069] S1: PVC powder, composite filler, cold-resistant agent, liquid rubber, silicone material, stabilizer, lubricant, flame retardant and UV resistant agent are mixed, and modifier is gradually added at 110°C to obtain a premix;

[0070] S2: The premix and the plasticizer are mixed at 85° C., and then extruded through a single screw extruder to obtain a PVC composite material.

[0071] Example 2

[0072] The PVC composite material of this embodiment includes the following components in parts by weight:

[0073]

[0074]

[0075] The composite filler comprises nano-grade clay, nano-active calcium carbonate, zirconium oxide and glass fiber in a mass ratio of 5:11:0:05:0.1.

[0076] The preparation method of the PVC composite material in this embodiment has the same steps as the preparation method in Example 1.

[0077] Example 3

[0078] The PVC composite material of this embodiment includes the following components in parts by weight:

[0079]

[0080] The composite filler comprises nano-grade clay, nano-active calcium carbonate, zirconium oxide and glass fiber in a mass ratio of 8:12:0.2:0.03.

[0081] The preparation method of the PVC composite material in this embodiment has the same steps as the preparation method in Example 1.

[0082] Example 4

[0083] The PVC composite material of this embodiment includes the following components in parts by weight:

[0084]

[0085]

[0086] The composite filler comprises nano-grade clay, nano-active calcium carbonate, zirconium oxide and glass fiber in a mass ratio of 10:15:0.04:0.05.

[0087] Comparative Example 1

[0088] The components of the PVC material of this comparative example are mostly the same as those of the PVC composite material of Example 1, except that: this comparative example does not contain a composite filler.

[0089] The preparation method of the PVC material in this comparative example is the same as the preparation method in Example 1.

[0090] Comparative Example 2

[0091] The components of the PVC material of this comparative example are mostly the same as those of the PVC composite material of Example 1, except that the composite filler of this comparative example does not contain nano-scale clay.

[0092] The preparation method of the PVC material in this comparative example is the same as the preparation method in Example 1.

[0093] Comparative Example 3

[0094] The components of the PVC material of this comparative example are mostly the same as those of the PVC composite material of Example 1, except that the composite filler of this comparative example does not contain nano-grade active calcium carbonate.

[0095] The preparation method of the PVC material in this comparative example is the same as the preparation method in Example 1.

[0096] Comparative Example 4

[0097] The components of the PVC material of this comparative example are mostly the same as those of the PVC composite material of Example 1, except that the composite filler of this comparative example does not contain zirconium oxide.

[0098] The preparation method of the PVC material in this comparative example is the same as the preparation method in Example 1.

[0099] Comparative Example 5

[0100] The components of the PVC material of this comparative example are mostly the same as those of the PVC composite material of Example 1, except that the composite filler of this comparative example does not contain glass fiber.

[0101] The preparation method of the PVC material in this comparative example is the same as the preparation method in Example 1.

[0102] The performance tests were conducted on the PVC composite materials of Examples 1-4, the PVC materials of Comparative Examples 1-5, and conventional PVC materials for light strips on the market. The test results are shown in Table 1.

[0103] Table 1

[0104]

[0105] It can be seen from Table 1 that, compared with the PVC materials of comparative examples 1-5 and conventional PVC materials for light strips, the PVC composite materials of the application examples are added with silicone materials and composite fillers, and have good low temperature resistance. The addition of nano-active calcium carbonate has a good improvement effect on the tensile strength and elongation at break of the PVC material for the light strip. Compared with Examples 1-4, it can be seen that the addition of nano-grade clay, zirconium oxide and glass fiber can effectively improve the thermal stability of the material and reduce the thermal deformation of the material.

[0106] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A PVC composite material, characterized in that: The composition comprises the following components in parts by weight: PVC powder 90-120 parts; 8-12 parts of composite filler; Plasticizer 60-80 parts; 8-12 parts of cold-resistant agent; 20-30 parts of liquid rubber; 4-8 parts of modifier; 0.5-1.0 parts of silica gel material; Other additives 0.1-15 parts; The composite filler comprises nano-grade clay, nano-active calcium carbonate, zirconium oxide and glass fiber; in: The mass ratio of nano-grade clay, nano-active calcium carbonate, zirconium oxide and glass fiber in the composite filler is (5-10):(10-15):(0.01-0.2):(0.02-0.1); The other additives include the following components in parts by weight: 2.5-4 parts of stabilizer, 0.1-0.5 parts of lubricant, 6-10 parts of flame retardant, and 0.5-0.8 parts of anti-UV agent.

2. The PVC composite material according to claim 1, characterized in that: The PVC includes Formosa Plastics S-70; The plasticizer includes at least one of trioctyl trimellitate, trihexyl trimellitate, and tetramethyl pyromellitate; The cold-resistant agent includes cold-resistant agent 797S and / or epoxy 1,4-cyclohexanedimethanol dioleate.

3. The PVC composite material according to claim 1, characterized in that: The modifier is modifier TPR; The silicone material is powdered vulcanized silicone.

4. The PVC composite material according to claim 1, characterized in that: The stabilizer includes stabilizer A-200P; The lubricant is lubricant 316A; The flame retardant is flame retardant DR-65; The anti-UV agent includes at least one of UV-326, UV-531, and BASF C81.

5. A method for preparing the PVC composite material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Mix PVC powder, composite filler, cold-resistant agent, liquid rubber, silicone material and other additives, gradually add modifier at 95°C-110°C, mix to obtain premix; The premix is ​​mixed with a plasticizer at 75° C.-85° C., and then extruded through a single-screw extruder to obtain the PVC composite material.

6. A light strip, characterized in that: The method is made of the PVC composite material as claimed in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Flame-proof polyvinyl chloride conveyer belt

    CN101172537A

  • composite

    DE102014113931A1